Castleman disease-associated diffuse parenchymal lung disease: A STROBE-compliant retrospective observational analysis of 22 cases in a tertiary Chinese hospital. Issue 39 (September 2017) - Huang, Hui; Feng, Ruie; Li, Jian; Song, Xinyu; Li, Shan; Xu, Kai; Cao, Jian; Zhang, Lu; Bi, Yalan; Xu, Zuojun
Abstract : Abstract: Intrathoracic involvement is common in Castleman disease (CD), but CD-associated diffuse parenchymal lung disease (DPLD) is rare and not well-reported. We conducted a retrospective analysis of 262 CD patients with a definite pathological diagnosis who were hospitalized between 1999 and 2015. Twenty-two CD patients had DPLD based on chest computed tomography (CT) scans. Among them, 9 were male and 13 were female, with a mean age of 45.3 years. Coughing (72.7%), fever (68.2%), and dyspnea (59.1%) were the common clinical manifestations. In high-resolution CT, obvious lymphadenopathy (81.8%) was the most frequent, followed by multiple nodules of different sizes (72.7%), cysts (59.1%), and patches of ground-glass opacity (54.5%). Six patients had lymphocytic interstitial pneumonia (LIP)-like CT images. Superficial lymph node biopsies (63.6%), video-assisted thoracic surgery lung biopsies (27.3%), CT-guided percutaneous lung biopsies (9.1%), and endoscopic lymph node biopsies (9.1%) were performed to make final diagnoses. The hyaline vascular variant (27.3%), the plasma cell variant (63.6%), and the mixed variant (9.1%) were the pathological subtypes. All but 2 were prescribed chemotherapy, and none was administered anti-interleukin-6 therapy. Among them, 14 patients improved, 3 died, 2 were stable, 2 were refractory, and 1 was lost to follow-up. Chinese CD-associated DPLD might be more prevalent in middle-aged female patients, with most cases being the plasma cell variant. Although a LIP-like pattern was reported, only one-quarter of the patients showed LIP-like CT images. Multiple nodules (especially solid nodules), cysts, and patchy areas were the common pulmonary radiological findings. More than half of the patients improved after chemotherapy. A well-designed prospective study should be performed to confirm these results.